"Opportunistic" spin-offs in the aftermath of an adverse corporate event. Issue 4 (21st November 2016) - Curran, Declan; O'Gorman, Colm; van Egeraat, Chris
Abstract : Purpose: The purpose of this paper is to explore the inter-organisational dynamics, in terms of the triggers to spin-off formation and the genealogical inheritance of spin-offs, between a parent characterised by an adverse event and the spin-offs that emerge. The study focusses on the nature of the triggering event, exploring the heterogeneous nature of the processes by which some spin-offs are formed to exploit new opportunities created unexpectedly by an adverse event, and on the genealogical inheritance that forms the pre-entry experience of the founder. Design/methodology/approach: A case study based on interview data with founders of spin-offs, supplemented with interviews with managers and industry experts, and with secondary data sources. The case study is of the spin-offs from a successful firm, Élan Corporation, reported to be the world's 20th largest drug firm in 2002, that experienced an adverse event in 2002. The Élan case offers the opportunity to focus exclusively on what Buenstorf (2009) refers to as necessity spin-offs. Prior to collecting data it was necessary to identify the population of spin-offs from Élan. Findings: This study extends existing research by identifying "opportunistic spin-offs": spin-offs that occur in the wake of an adverse event where the entrepreneur exploits an unexpected opportunity to engage in entrepreneurship but does not feel compelled to establish the spin-off. These spin-offs are characterised by "unexpected opportunities", "opportunistic acquisition of assets" and, perhaps reflecting the seniority and experience of those involved, "alternative employment opportunities". Originality/value: Understanding the process of spin-off formation is important because it provides insight into how and why individuals initiate new ventures. Spin-offs are an important source of new firms and an important mechanism in the process of industry evolution. The study contributes to the literature on spin-offs by providing evidence of the heterogeneous nature of spin-offs that occur in the aftermath of an adverse event, leading to the classification of some spin-offs as "opportunistic spin-offs". The study contributes to the entrepreneurship literature by demonstrating that an important trigger for venture creation is unexpected changes in an individual's employment circumstances.